2020
DOI: 10.1097/pas.0000000000001492
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immunohistochemistry for PRAME With Cytogenetic Test Results in the Evaluation of Challenging Melanocytic Tumors

Abstract: PRAME (PReferentially expressed Antigen in MElanoma) is a melanoma-associated antigen. Although diffuse immunoreactivity for PRAME is found in most primary cutaneous melanomas, melanocytic nevi express PRAME usually only in a subpopulation of tumor cells or not at all. Hence, testing for PRAME expression has the potential to provide useful information for the assessment for diagnostically ambiguous melanocytic neoplasms. Many of the latter tumors are currently studied by cytogenetic methods for ancillary evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
155
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(169 citation statements)
references
References 31 publications
12
155
2
Order By: Relevance
“…A summary of PRAME results by type of lesion is provided in We note that the threshold for defining diffuse staining in our cohort (60%) differs from the cutoff of 75% established by Lezcano et al 14,15,19 Six of our 24 non-spitzoid melanomas (25%), none of which were desmoplastic, would be considered non-diffuse with the higher In summary, this study expands on the diagnostic utility of PRAME by demonstrating its lack of diffuse expression in atypical but benign melanocytic proliferations, facilitating their distinction from melanoma. This study also reinforces that PRAME expression in spitzoid neoplasms should be interpreted in the context of histopathologic features, and correlation with cytogenetic and/or molecular studies may be required for diagnostic classification.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…A summary of PRAME results by type of lesion is provided in We note that the threshold for defining diffuse staining in our cohort (60%) differs from the cutoff of 75% established by Lezcano et al 14,15,19 Six of our 24 non-spitzoid melanomas (25%), none of which were desmoplastic, would be considered non-diffuse with the higher In summary, this study expands on the diagnostic utility of PRAME by demonstrating its lack of diffuse expression in atypical but benign melanocytic proliferations, facilitating their distinction from melanoma. This study also reinforces that PRAME expression in spitzoid neoplasms should be interpreted in the context of histopathologic features, and correlation with cytogenetic and/or molecular studies may be required for diagnostic classification.…”
Section: Resultsmentioning
confidence: 77%
“…18 Lezcano et al more recently showed a strong concordance between PRAME expression and cytogenetic studies in ambiguous melanocytic neoplasms. 19 In that study, PRAME was reported as scores designating diffuse or non-diffuse staining for an aggregated group of neoplasms. Further study of the pattern of PRAME expression in diagnostically challenging melanocytic lesions is merited.…”
mentioning
confidence: 99%
“…Since the diagnosis of primary Spitzoid melanoma by conventional methods (for example, conventional ABCDE [asymmetry, border irregularity, color variation, diameter >6 mm, and evolution] criteria, dermoscopy, histopathological diagnosis by HE staining) is challenging [ 2 , 5 ], recently, several diagnostic tools were developed [ 5 , 6 , 7 , 8 , 9 , 10 ]. Indeed, Bahrami et al [ 5 ] reviewed the molecular biology of pediatric melanoma, including Spitzoid melanoma, suggesting that the specific kinase gene fusion (including NTRK1, NTRK3, ALK, ROS1, RET, MET, and BRAF) might be useful for the diagnosis of Spitzoid melanoma [ 5 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although these molecular biological methods are useful for the diagnosis of Spitzoid neoplasm, institutes that can employ these expensive methods are limited. Notably, Lezcano et al [ 2 ] evaluated the IHC of PRAME for challenging melanocytic tumors, including Spitzoid melanoma, by cytogenetic test, and the result suggested the high sensitivity (75.0%) and specificity (98.8%) of PRAME IHC for the diagnosis of Spitzoid melanoma. This report suggested the use of PRAME IHC as a supportive test in the evaluation of pediatric melanoma including Spitzoid melanoma [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation